Analisis Pengaruh Durasi Tidur terhadap Tingkat Konsentrasi Mahasiswa Akhir BPI Tahun 2025 - Alfiyyah, Alfiyyah; Farid Kamal; Firdha Hayrany; Siva Nurfariza (CV. ITTC INDONESIA, 2025)
Sleep is a basic biological need of humans that functions to restore both physical and mental energy. This study aims to analyze the effect of sleep duration on the concentration levels of final-year students in the Islamic Guidance and Counseling Study Program (BPI) of 2025. The background of this research is the importance of concentration in the process of completing final assignments, as well as the potential disruption of concentration due to irregular sleep patterns. The research method used is a correlational quantitative method employing data collection techniques through an online questionnaire. The research sample consisted of 36 final-year BPI students. The results of the analysis conducted using the Pearson correlation test showed a correlation coefficient value of 0.521 with a significance value (p) of 0.001 < 0.05. This indicates a significant relationship between sleep duration and concentration levels. The conclusion of this study is that sleep duration has a positive effect on the concentration levels of final-year students. Therefore, it is recommended that students establish a healthy sleep pattern to support academic productivity.